(untitled) (MAUSAM, 1982)
The dry farming tract in India, where the annual rainfall varies from 400 to 1000 mm, comprises of 87 districts in 9 States. In this tract rainfall is the limiting factor for successful raising of crops. In order to stabilise the crop at a certain level even in a low rainfall year , it is essential that agricultural planning is drawn up on a rational scientific basis in terms of climatic potential of the area. For this purpose, amongst other things, it is necessary to know the minimum assured rainfall week by week. Weekly rainfall has, therefore, been subjected to statistical analysis by Incomplete Gamma distribution and minimum assured rainfall has been worked out at different probability levels from 10 to 90 per cent. Important features noticed on assured rainfall have been discussed in detail. The entire tract has been broadly divided into 7 homogeneous rainfall pattern zones. The duration of crop period in each zone has been indicated based on assured rainfall alone.